Phrasal Verbs: Tips for ESL Learners / Dr. Rafidah Kamarudin ... [et al.]. - Kamarudin, Rafidah; Abdullah, Amalia Qistina Castañeda; Zainal Arifin, Mazliyana; Zuraimi, Nur’Ain (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
"Carried out an experiment" or "performed an experiment"? "The writers emphasise" or "The writers point out"? Despite this language feature's common and frequent use in written and spoken discourse, many find it difficult to decide whether to use a phrasal verb or its one-word counterpart. The struggle to use this language form is even greater among English language learners. There are some useful and helpful tips to help language learners understand and utilise this language form. Undeniably, most phrasal verbs tend to have an informal style or a more casual tone. For instance, phrasal verbs like "show off," "give up," or "hang out." However, it is not right to assume that a single verb is always better than phrasal verbs, as there are cases in which phrasal verbs are much more appropriate than their one-word counterparts. For instance, ‘the teacher found out about the student’s strange behaviour instead of ‘the teacher discovered about the student’s strange behaviour’ or ‘the car sped up’ instead of ‘the car accelerated’.